Analisa Base Shear Pada Struktur Gedung Bertingkat Menggunakan Sistem Rangka Pemikul Momen Khusus (SRPMK) Berdasarkan SNI 1726-2019 dan SNI 1727-2020 - M Helmi Ananda Saputra; Robi Sahbar; Pujiono T (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Base shear is one of the main parameters in the analysis and design of earthquake-resistant building structures. This parameter is particularly important in the Special Moment Resisting Frame (SMRF) system, which is known for its high ductility and good energy dissipation capacity, making it widely applied to buildings in earthquake-prone areas. This study aims to analyze the magnitude of base shear in buildings with the SMRF system based on the provisions of SNI 1726:2019, taking into account several factors, including the total mass of the structure, the fundamental period, the importance factor of the building, soil conditions, as well as the seismic response coefficient modified by the response modification factor according to the structural system used. The research employed a numerical analysis approach using structural modeling software, where the design seismic forces were calculated based on the relevant seismic parameters. The results show that the base shear value is significantly influenced by the mass of the structure and the fundamental period of the building, as well as variations in response spectrum values due to different soil conditions. The analysis also highlights the importance of selecting appropriate importance factors and response modification factors to ensure both safety and efficiency in structural design. In conclusion, this study emphasizes that the implementation of the provisions in SNI 1726:2019 is crucial in determining accurate base shear values. This not only has implications for the structural resistance of buildings against seismic loads but also for occupant safety and the sustainability of building functions in earthquake-prone regions.